Sociedade Emancipadora 27 de Fevereiro: um movimento abolicionista na cidade de Santos - 1886 - 1888 - Dias, Vera Lucia Alba Rei (2014)
The aim of the present work is to reveal the origins of Santos city as the land goodness and charity . The abolitionist fight is an important part of it and, because of that, it was told that there was a law, in 1886, able to end slavery in its perimeter, but the sources did not confirm it. The history and the main actors of Sociedade Emancipadora 27 de Fevereiro are important aspects of the present dissertation, with his idiosyncrasies, as well as the Camara Municipal role and daily life facts about ordinary people at that time. The intense social movements and transformations at the end of XIX century are also considered